Jejak Respon Pendidikan Islam di Indonesia terhadap Gelombang Globalisasi: Pemetaan Periodisasi, Sumber Tantangan, dan Pola Respon Historis - Lendy Fathmi Lia Syachputri; Assyifa Qori Lhegina; Nur Saidah (Lembaga Yasin AlSys, 2026)
Globalization has brought major changes to the educational landscape and has created both pressures and opportunities for Islamic education in Indonesia. This study aimed to examine how Islamic education responds to the dynamics of globalization through historical and cultural perspectives. Using a qualitative library research method, this article analyzed various national journal publications discussing the challenges, opportunities, and adaptive strategies of Islamic education in the context of global change. The review found that globalization exerts pressure through the flow of secular modernity that may weaken spiritual identity, while simultaneously offering opportunities through technological advancement, global collaboration, and the development of digital learning. Historically, Islamic education in Indonesia, from the pesantren tradition to modern Islamic higher education institutions, has demonstrated strong cultural resilience and an ability to adapt without abandoning core Islamic values. This review highlights the importance of strengthening curriculum integration, teacher professionalism, and digital literacy so that global engagement in Islamic education remains aligned with Islamic ethical values. The study concludes that Islamic education needs to reinforce an integrative paradigm, optimize the use of technology, and maintain moral-spiritual guidance to remain relevant, competitive, and transformative in the global era.